Structure of a new nucleic-acid-binding motif in eukaryotic transcriptional elongation factor TFIIS - Weiss, Michael A. (2012)
Transcriptional elongation involves dynamic interactions among RNA polymerase and single-stranded and double stranded nucleic acids in the ternary complex1–4. In prokaryotes its regulation pro-vides an important mechanism of genetic control1. Analogous eukaryotic mechanisms are not well understood5, but may control expression of proto-oncogenes6,7 and viruses, including the human immunodeficiency virus HIV-1 (ref. 8). The highly conserved euk-aryotic transcriptional elongation factor TFIIS9 enables RNA polymerase II (RNAPII) to read though pause or termination sites, nucleosomes and sequence-specific DNA-binding proteins10–14. Two distinct domains of human TFIIS, which bind RNAPII and nucleic acids, regulate read-through10 and possibly nascent transcript cleavage11–15. Here we describe the three-dimensional NMR16 structure of a Cys4 nucleic-acid-binding domain from human TFIIS9,10. Unlike previously characterized zinc modules17–21, which contain an α-helix, this structure consists of a three-stranded β-sheet. Analogous Cys4 structural motifs may occur in other proteins involved in DNA or RNA trans-actions22–24, including RNAPII itself25. This new structure, desig-nated the Zn ribbon, extends the repertoire of Zn-mediated peptide architectures26 and highlights the growing recognition of the β-sheet as a motif of nucleic-acid recognition27,28.